Effects of Additional Radial Shockwave Therapy to Median Nerve Gliding Exercises on Hand Grip Strength in Carpal Tunnel Syndrome Patients - Cornelia Arina Pradipta; Rudy Handoyo; Hari Peni Julianti; Hindun Zuhdiana; Noviolita Dwi Kusumawati (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Carpal Tunnel Syndrome (CTS) is one of the most common entrapment neuropathiesfound in the upper extremities. Patients with moderate and severe CTS usually experience disturbancesin motor strength. A non-invasive therapeutic method that has recently emerged in the treatment of CTSis Radial Shock Wave Therapy (RSWT). RSWT is a therapy using shock waves and can be added to otherforms of exercise. The addition of RSWT in CTS is expected to increase the grip strength. Research thatdirectly assesses the effect of adding RSWT and median nerve gliding exercises on hand grip strength inCTS patients has not been conducted.Methods: This study was a pre-test/post-test control group design. There were 22 moderate grade CTSsubjects divided into 2 groups, the control group was received median nerve gliding exercise (n=11) andthe treatment group was received additional RSWT on median nerve gliding exercise (n=11). Assessmentof grip strength by Jamar hand dynamometer was performed before and after 4 weeks of treatment. Themean differences before and after treatment, as well as between groups was compared statistically usingan unpaired t-test.Results: There was no significant difference in the handgrip strength of the control group (p = 0.094),and a significant difference in the treatment group (p = 0.009) before and after the intervention. However,there were no significant differences in grip strength between the two groups (p=0.065).Conclusion: There was no significant effect of adding RSWT on improving handgrip strength in CTSpatients who received a median nerve gliding exercise.Keywords: carpal tunnel syndrome, entrapment neuropathies, grip strength, nerve gliding exercise,radial shockwave therapy